PELATIHAN PEMBINA UKS UNTUK MENINGKATKAN PERAN UKS DI SDN 5 SUMERTA DENPASAR - Komang Trisna Sumadewi; Desak Putu Citra Udiyani; D.A.A.A Suka Astini (JURNAL SEWAKA BHAKTI, 2020)
Besides functioning as a place to study, schools are also at risk as a place for disease transmission if not managed properly. Primary school age children are vulnerable to infectious or non-communicable diseases such as accidents when playing. Therefore, the inculcation of values ​​of healthy and clean living behavior from an early age is very important to avoid various disease risks, one of which is through the School Health Efforts (UKS) approach. The partner in this service is the Trustee of UKS in SDN 5 Sumerta. So far the partners have never received any explanation regarding the implementation of the UKS. The method that will be used is focus group discussion (FGD), interactive dialogue, training methods and mentoring. FGD aims to find problems faced by partners. Training and mentoring are carried out on an ongoing basis accompanied by monitoring and evaluation which is carried out regularly every month to partners in accordance with the form that has been prepared and carried out by the service team. This program has been implemented well judged by the implementation of activities on time, good involvement and cooperation on the part of SDN 5 Sumerta.